A Preliminary Recorded of Fishes at Selected Headwater Streams Before Establishing of Royal Belum State Park, Perak - Amir Shah Ruddn Md Sah; Mohd Zambri Mohd Akhir; M S Shahrul Anuar; Ahyauddin Ali (Indonesian Society of Limnology, 2023)
A total of 30 fish species from 14 families were recorded during the survey at selected headwater streams of Belum Forest Reserve of Temengor Reservoir between June to December 1998. Family Cyprinidae was the dominant family which contributed 46.7% followed by Channidae (10.7%) and Bagridae (6.7%). Out of 30 species, only four species such as Devario regina, Rasbora paviana, Osteochilus hasselti and Hampala macrolepidota were sampled from all sampling stations. One specimen of freshwater puffer fish, Poa leiurus, was recorded at Sungai Ta eng. Distance, water velocity, river depth, types of substrate and physio-chemical parameter played an important role in determining species composition, diversity, biomass and species distribution. As there are many headwater streams in Temengor Reservoir still unexplored, the fish species number at Temengor Reservoir assume higher than been recorded before.